Decision support system framework for feasibility study in construction project - Mohd. Nazari, Nurjuliana (2007)
The construction projects present a unique situation where each project is different with different situation and parties. One of the important stage involve in a construction project is the preparation of the feasibility study. Feasibility study needs a lot of information and the process to analyze the information is tedious and time consuming. The decision support system (DSS) is an attempt to simplify the analyzing process and to reduce the time needed in preparing the study. The aim of this research is to proposed Decision Support System Framework particularly for quantity surveying consultants to improve the effectiveness of the decision making process. The objectives of the study are to identify the current practice of decision making process in the feasibility study of construction project, to identify the DSS that is able to improve the decision making process in the feasibility stage and to develop a Decision Support System Framework for feasibility study. The information gathered for the first and the second objectives mainly via interviews and internet sources were used as a guideline to develop the framework. The framework was developed based on the DSS identified during the second objectives. The framework of the system provides terminology, concepts and guidelines that are useful to apply the system. By understanding the factors considered for the study as the area of application for the DSS, the type of DSS application are able to be identified, that is the cost estimation DSS. Then, the requirement of the cost estimation DSS identified that is the Crystal Ball are gathered to complete the framework. The framework can be use as a guideline to develop the prototype of the system and as a guide to apply the system